Inside the kaleidoscope: unravelling the “feeling different” experience of bicultural bilinguals - Purpuri, Silvia; Mulatti, Claudio; Filippi, Roberto; Treccani, Barbara (Frontiers in Psychology, 2024)
This article explores the phenomenon of “feeling different” experienced by bicultural bilingual individuals when they switch between their two different languages. Available data suggests that this experience is genuine and holds substantive value, not merely anecdotal. While on one hand, such a feeling may stem from the fact that the two languages were acquired at different times in individuals’ lives (with all that entails in terms of efficiency and empowerment in using the two languages), on the other hand, it seems to entail deeper differences linked to the differential activation of cultural values, behavioral patterns, and expectations when the two languages are used. Its manifestations seem to be influenced by a variety of factors beyond just language choice, including the context in which this choice is performed. Results of studies investigating the experience of feeling different also suggest that it can lead to a sense of exclusion, isolation or marginalization within one’s own community. However, this experience more often yields positive outcomes, with individuals perceiving it as enriching and contributing positively to both their personal development and the broader societal fabric. Amid contemporary challenges related to immigration, the study of biculturalism and related psychological phenomena, such as the “feeling different” experience, becomes imperative, as it may provide insights into how individuals navigate the complexities linked to their cultural identities.